2007
DOI: 10.1007/s00383-007-1887-9
|View full text |Cite
|
Sign up to set email alerts
|

Inchin-ko-to prevents medium-term liver fibrosis in postoperative biliary atresia patients

Abstract: The oriental herbal formulation inchin-ko-to (ICKT) inhibits liver cell apoptosis induced by transforming growth factor-beta 1 (TGF-beta1). This study evaluated the effect of ICKT on serum markers of liver function and liver fibrosis in postoperative biliary atresia (BA) patients. Twenty-one postoperative BA patients with elevated GOT, GPT and gamma-GTP, but normal serum total bilirubin levels, were divided into two groups arbitrarily; an ICKT group (n = 12), and a no-ICKT group (n = 9). Serum markers of liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Inchinkoto has long been used to treat various liver disorders in eastern Asia such as Japan and China [5] [6] [7] [8] [9]. Iinuma, et al reported that Inchinkoto might have a protective and antifibrotic effect for the liver of children with biliary atresia [6] [7].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inchinkoto has long been used to treat various liver disorders in eastern Asia such as Japan and China [5] [6] [7] [8] [9]. Iinuma, et al reported that Inchinkoto might have a protective and antifibrotic effect for the liver of children with biliary atresia [6] [7].…”
Section: Discussionmentioning
confidence: 99%
“…Iinuma, et al reported that Inchinkoto might have a protective and antifibrotic effect for the liver of children with biliary atresia [6] [7]. Though the precise mechanisms of its action on the liver diseases remain unknown, it can be speculated as following: 1) inhibition of hepatocyte apoptosis induced by transforming growth factor-β1 [10]; 2) inhibition of the production of inflammatory cytokines and inducible nitric oxide synthase [11] [12]; and 3) direct suppression of liver fibrosis [13].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…31 Modulation of this biological process would have immense benefit, but seems elusive and far distant. Asian centres routinely prescribe the Chinese herb Inchinko-to; claimed benefits include inhibition of apoptosis and liver fibrosis, 32 but real evidence of benefit remains unpublished.…”
Section: Limitation Of Hepatic Fibrosismentioning
confidence: 99%